EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SAINTIFIK PADA POKOK BAHASAN HIMPUNAN DITINJAU DARI KECERDASAN EMOSIONAL KELAS VII SMP NEGERI DI KABUPATEN SUKOHARJO - Fakhri Auliya, Nanang Nabhar; Budiyono, Budiyono; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objective of this research was to know the effect of the learning models on the learning achievement in Mathematics viewed from the emotional quotient of the students. The learning models compared were the cooperative learning model of the NHT type with scientific approach, the Cooperative Learning Model of the TPS type with scientific approach, and the classical model with scientific approach. This research used the quasi experimental research. Itâs population was all of the students in Grade VII of State Junior Secondary Schools in Sukoharjo. The samples of the research were taken by using the stratified cluster random sampling technique and consisted of 262 students. They were grouped into three classes, namely: 92 students in Experimental Class 1, 85 students in Experimental Class 2, and 85 students in Control Class. The instruments to gather the data were test of achievement in Mathematics on the learning topic of Set, and emotional quotient questionnaire. The proposed hypotheses of the research were analyzed by using the two way analysis of variance with unbalanced cells. The results of the research were as follows. 1) The cooperative learning model of the NHT type with scientific approach results in a better learning achievement in Mathematics than the cooperative learning model of the TPS type with scientific approach, and the classical model with scientific approach, the cooperative learning model of the TPS type with scientific approach results in a better learning achievement in Mathematics than the classical model with scientific approach. 2) Emotional quotient gives students a different effect on mathematics achievement of students in the topic of Set. The students with the high emotional quotient have a better learning achievement in Mathematics than those with the moderate emotional quotient and those with the low emotional quotient, the students with the moderate emotional quotient have a better learning achievement in Mathematics than those with the low emotional quotient. (3) There was not an interaction the aforementioned learning models and the categories of the emotional quotient on the learning achievement in Mathematics of the students.Keywords: NHT, TPS, Classical, Scientific Approach and Emotional Quotient.